Impacts of Temperature Measurements From Sea Turtles on Seasonal Prediction Around the Arafura Sea - Doi, Takeshi; Storto, Andrea; Fukuoka, Takuya; Suganuma, Hiroyuki; Sato, Katsufumi (Frontiers in Marine Science, 2019)
In this work, we added the assimilation of subsurface temperature measurements obtained from sea turtles around the Arafura Sea from June to October 2017 into an operational seasonal prediction system. The impact of these measurements was explored by conducting the so-called ocean observing system experiments. It was found that the prediction of regional sea surface temperatures around the Arafura Sea is significantly improved at 3-4 months lead-time. The results also showed that the addition of temperature measurements from sea turtles into the existing Global Ocean Observing System (including satellites, mooring buoys, ships, and profiling floats) may open a new door to improving regional seasonal prediction through better representation of the initial state of the upper ocean.